Clinical sequencing identifies potential actionable alterations in a high rate of urachal and primary bladder adenocarcinomas. (20th January 2023) - Varadi, Melinda; Nagy, Nikolett; Reis, Henning; Hadaschik, Boris; Niedworok, Christian; Modos, Orsolya; Szendroi, Attila; Ablat, Jason; Black, Peter C.; Keresztes, David; Csizmarik, Anita; Olah, Csilla; et al.
Abstract: Objective: Administration of targeted therapies provides a promising treatment strategy for urachal adenocarcinoma (UrC) or primary bladder adenocarcinoma (PBAC); however, the selection of appropriate drugs remains difficult. Here, we aimed to establish a routine compatible methodological pipeline for the identification of the most important therapeutic targets and potentially effective drugs for UrC and PBAC. Methods: Next‐generation sequencing, using a 161 cancer driver gene panel, was performed on 41 UrC and 13 PBAC samples. Clinically relevant alterations were filtered, and therapeutic interpretation was performed by in silico evaluation of drug‐gene interactions. Results: After data processing, 45/54 samples passed the quality control. Sequencing analysis revealed 191 pathogenic mutations in 68 genes. The most frequent gain‐of‐function mutations in UrC were found in KRAS (33%), and MYC (15%), while in PBAC KRAS (25%), MYC (25%), FLT3 (17%) and TERT (17%) were recurrently affected. The most frequently affected pathways were the cell cycle regulation, and the DNA damage control pathway. Actionable mutations with at least one available approved drug were identified in 31/33 (94%) UrC and 8/12 (67%) PBAC patients. Conclusions: In this study, we developed a data‐processing pipeline for the detection and therapeutic interpretation of genetic alterations in two rare cancers. Our analyses revealed actionable mutations in a high rate of cases, suggesting that this approach is a potentially feasible strategy for both UrC and PBAC treatments. Abstract : Precision oncology is an emerging treatment strategy for rare cancers such as urachal (UrC) and primary bladder adenocarcinoma (PBAC). In this study, we performed a multicentre sample collection and developed a DNA sequencing (161 gene Oncomine Comprehensive Assay Panel) and data processing pipeline for the detection and therapeutic interpretation of targetable genetic alterations in these two rare cancer entities. Our analyses revealed actionable alterations (e.g. EGFR, BRCA, CCND1/2/3, ERBB2, MET and METex14 ) in a high rate of cases, suggesting this approach to be feasible for both UrC and PBAC.